Pengelolaan Keuangan Pribadi Menggunakan Teknologi Citra Digital Berbasis Website - Heri Purwanto; Rikky Wisnu Nugraha; Deden Sofyan Hamdani; Mohamad Rizky (Labkat Press KA FTIK UNIKOM, 2022)
Financial management is an action to meet future financial needs and can also be used to solve personal and group economic problems. Financial management is needed to deal with financial problems that occur in life. Increasing daily expenses are one of the reasons for the importance of managing personal finances so you don't get stuck in debt. The community is also not used to managing their finances, so they are often burdened with unexpected expenses. By managing the right finances, it can be useful to help the implementation of each individual goal. This study aims to develop applications that have been previously designed by previous researchers, the system is made on a website-based basis for user flexibility, and features are added using digital image technology to add input features for financial income and expenditure data in the form of money scans and shopping receipt scans. The methodology used in this research is the Agile method, this methodology focuses on customer satisfaction and also the speed of program development. The data collection technique uses literature study and the modeling language used is the Unified Modeling Language (UML). Based on the test results, this system can be accessed through various operating systems that have an internet connection and a browser, making it easier for users to take advantage of the various facilities in the system. This system can be developed further by adding features that can remind users of the use of money, such as notifications about limits on financial use.